Perezhivanie as a source of children’s development: case of emotional development intervention through visual arts - Margarita Gavrilova; Dmitry Kornienko (Frontiers in Psychology)
Recent theoretical ideas emphasise the non-direct environmental influences on child development. Environmental factors affect child development by the principle of refraction rather than by the principle of reflection: any environmental condition is refracted in a child’s mind in unique ways depending on his or her actual abilities and personal attitude to the situation. Complexity and multidimensionality of the relationship between environment and psychological prosseses poses a great challenge to the researchers. This paper provides a theoretical analysis and justification of the prospective use of the concept of ‘perezhivanie’, as a tool for theoretical analyses of child development and a practical phenomenon that allows to explore how a child interprets and emotionally relates to certain events or moments in the environment. Perezhivanie is considered as the unit of analysis of consciousness in cultural-historical theory. A case study of an intervention in emotional development through visual arts is presented as an illustration of using the concept of ‘perezhivanie’ to design practical sessions with children and to analyse the way in which their minds work in learning processes. The findings suggest that the study of perezhivanie for theoretical and practical purposes is promising, as this phenomenon can provide rich data on how a child interprets and relates to a particular event or moment in the environment.